1992
DOI: 10.1530/acta.0.1260489
|View full text |Cite
|
Sign up to set email alerts
|

Cabergoline in the long-term therapy of hyperprolactinemic disorders

Abstract: in the longterm therapy of hyperprolactinemic disorders. Acta Endocrinol 1992:126:489-94. The efficacy and safety of the new long-acting dopamine agonist cabergoline were evaluated in 127 hyperprolactinemic patients (124F and 3M; 71 with microprolactinoma, 14 with macroprolactinoma, 5 with operated macroprolactinoma and 37 with idiopathic disorder) who were treated with the drug for from 3 to 52 months (median, 14 months). Cabergoline was administered orally at dose levels ranging between 0.2 and 3.5mg per we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
59
2
5

Year Published

1994
1994
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(73 citation statements)
references
References 24 publications
7
59
2
5
Order By: Relevance
“…These outcomes are better than usually been reported (mean 29%, ranging from 7 to 69% [5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…These outcomes are better than usually been reported (mean 29%, ranging from 7 to 69% [5][6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Discussioncontrasting
confidence: 55%
“…In general, most studies have reported remission rates of 17-35%, with variable follow-up times of 12-60 months [7,8,[12][13][14][15][16]. A prospective study by Colao et al [18] including 200 hyperprolactinemic patients reported recurrence rates of 31% in those with micro-and 36% in those with macroprolactinomas at 2-5 years of follow-up after cabergoline withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…These success rates are similar to those of other studies (73-90 vs. 59%) evaluating micro-and macroprolactinomas together (15)(16)(17)(18). When the patients were analyzed after being divided into two groups (idiopathic + microprolactinoma, and macroprolactinoma), the success rate in the bromocriptine-treated idiopathic + microprolactinoma subgroup was 62%, similar to the 70%rate observed by van der Heijden et al (19), and higher than the 48% rate reported by Pascal-Vigneron et al (20).…”
Section: Discussionsupporting
confidence: 90%
“…1,11 Although a direct trial comparing bromocriptine with cabergoline is lacking, the results obtained with the latter drug seem even better. In one study, 31% of patients with microprolactinoma had normal PRL levels one year after discontinuation of therapy, 12 whereas in another large study, 69% of 105 patients with microprolactinoma had no recurrence of hyperprolactinaemia two years after stopping cabergoline. 10 These excellent results were obtained in a selected group of highly responsive patients who also had favourable tumour characteristics on magnetic resonance imaging (MRI).…”
Section: W I T H D R a W A L O F D O P A M I N E R G I C D R U G Smentioning
confidence: 98%